Study on the adhesive property of sludge-modified magnesium phosphate cement reinforcement coating for steel bars - Shusen, Zhang; Jiapeng, Yang; Yiyang, Li; Zhenyu, Wang; Shunjie, Zhong; Liling, Zhuang; Tao, Wang (Frontiers in Materials, 2024)
The synergistic interaction inreinforced concrete systems originates from the strong bond between steel reinforcement and concrete, enabling them to collaborateunder load and optimize structural performance. This study applied various sludge-modified magnesium phosphate cement mixtures to the surfaces of plain round steel bars and ribbed steel bars to prepare steel-reinforced concrete specimens. The characterization of the bond performance of the sludge-modified magnesium phosphate cement reinforcement coating for steel bars and concrete was achieved through analyzing the failure modes, bond strength, and slip values of different groups. Microscopic analysis was performed using a scanning electron microscope. The results revealed that the primary failure mode of the steel-reinforced concrete specimens was steel bar pull-out, with some specimens exhibiting concrete splitting failure. Coating application on plain round steel bars increased bond strength, while on ribbed steel bars, it decreased bond strength. The application of the coating slightly reduced slip values to some extent.